2019
DOI: 10.1111/clr.13407
|View full text |Cite
|
Sign up to set email alerts
|

Implant fracture failure rate and potential associated risk indicators: An up to 12‐year retrospective study of implants in 5,124 patients

Abstract: Objectives This study investigated fracture rates and risk indicators for fractures in internal connection dental implants. Material and Methods We performed a retrospective analysis of 19,006 internal connection implants used in fixed restoration in 5,124 patients (4,570 males, 554 females) at the Dental Hospital of Veterans Health Service Medical Center between 2006 and 2015. Patients were followed through June 2018 (0.03–12.39 years post‐installation). Clinical factors (age, sex, implant diameter, implant l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…Since panoramic radiography has been reported to be a simple and reliable method of measuring bone level changes, we assessed the implant failure threats at the points where the bones were attached to the implants using recall session panoramic radiographs 17 . In accordance with the results of previous investigations, we confirmed that age and sex were not associated with MBL 18,19 .…”
Section: Discussionsupporting
confidence: 93%
“…Since panoramic radiography has been reported to be a simple and reliable method of measuring bone level changes, we assessed the implant failure threats at the points where the bones were attached to the implants using recall session panoramic radiographs 17 . In accordance with the results of previous investigations, we confirmed that age and sex were not associated with MBL 18,19 .…”
Section: Discussionsupporting
confidence: 93%
“…Second, a relationship between the absence of hard tissue management and fracture of the abutment or implant was also found on univariate analysis (P = 0.040). Implants at the bone grafting sites reportedly have a low risk of fracture [38]. Because several factors are interrelated, it is considered that no association was found on multivariate analysis after adjusting for confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the fractured implants in this study were implants with a length greater than 11.5 mm. However, a study by Tabrizi et al [18] and Lee et al [21] reported no significant correlation between implant length and fixture fracture. Therefore, further research is necessary in this area.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, the number of cases was insufficient, but the diameter of the fractured implants varied in 2 cases by 3.8 mm, 3 cases by 4 mm, 5 cases by 4.5 mm, and 2 cases by 5 mm. However, it should be noted that many papers report that the smaller the diameter of the implant, the greater the possibility that fracture occurs [7,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%